Relation of Alcohol Consumption to Risk of Heart Failure in Patients Aged 65 to 84 Years With Hypertension - Sahle, B.; Owen, A.; Wing, L.; Beilin, L.; Nelson, M.; Jennings, G.; Reid, Christopher (Excerpta Medica, Inc, 2018)
Although a high level of alcohol consumption is associated with cardiomyopathy, the benefit or risk of moderate alcohol consumption on incident heart failure (HF) is unknown. This study examined the association between alcohol consumption and risk for HF in older adults with hypertension. The study analyzed data from a cohort of 6,083 participants aged 65 to 84 years at baseline (1995 to 2001) followed for a median of 10.8 years during and after the Second Australian National Blood Pressure Study. Frequency and amount of alcohol consumption were self-reported at baseline and during the clinical trial. The percentages of current drinkers, former drinkers, and never-drinkers at baseline were 4,400 (72%), 394 (6%), and 1,289 (21%), respectively. Incident HF was diagnosed in 183 men and 136 women. After adjustment for multiple confounders, alcohol consumption was not significantly associated with HF. Compared with never-drinkers, the adjusted hazard ratios (95% confidence interval) for those who consume 1 to 7, 8 to 14, and >14 drinks/week at baseline were 0.87 (0.59 to 1.30), 0.96 (0.57 to 1.60), and 0.71 (0.25 to 2.02), respectively in women, and 0.81 (0.47 to 1.38), 0.77 (0.43 to 1.38), and 1.04 (0.59 to 1.84), respectively in men. The findings of lack of an association between alcohol consumption and risk of HF persisted in the analyses comparing the risk of HF across each level of drinking at baseline or at follow-up with never-drinkers. In the present study, there was no evidence for benefit or risk of alcohol consumption, reported at baseline or at follow-up, in relation to incident HF in both men and women.